Data Acquisition with LoraWAN IoT Technology to Monitor Bio-Inspired Wind Turbines in Rural Areas of Cundinamarca - Quintero, Jersson A.; Parra Peñuela, Hector Guillermo; Gaona, Elvis E. (Ingeniería, 2022)
Context: The energy crisis is a global problem. In Colombia, research aimed at the efficient use of renewable energies is being conducted. For example, in the case of bio-inspired wind generators, a monitoring system is required to observe the output variables (voltage and frequency). Method: LoRaWAN technologies are used to deploy the wireless link since the generators are separated from the base station. In addition, the Gateway coverage area is simulated with HTZ Communications software for future smart grid improvements. Results: The implemented system allows constant monitoring over a long period of time and stores its information in online, open-source databases, which allows remotely visualizing the status of the network, with a total of 3 samples per minute and a range of up to 3,47 km. Conclusions: The data acquisition system can be implemented for remote monitoring. Moreover, since it is a low power system, it can be utilized in non-interconnected areas, as well as for storing data for up to 6 months. However, for the characterization of a model of wind generators, it is advisable to modify the system so that the sampling time is lower.